Article 377 and LGBT Activism in India: Controversies and Challenges (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Homosexuality Debating issues in the light of Indian legal and social system An investigative research The previously mentioned theme of my exploration work is fixated on the most dubious and criticized term 'homosexuality.' To present homosexuality is sentimental or sexual fascination or conduct among the general population of a similar sex. As a sexual introduction, homosexuality alludes to a persevering example or air to encounter sexual fondness or sentimental attractions essentially to individuals of a similar sex. It additionally alludes to a person's feeling of individual and social character dependent on those attractions, conduct communicating them, and participation in a network of other people who share them. The normal term utilized for gay people are 'gays', 'lesbians', 'bisexuals', or 'transgender' and on the whole known as LGBT individuals.